In-vitro Antibacterial Activity of Salacia oblonga Wall - P. Prayaga Murty*, T. Mallikarjuna Rao (Recent Research in Science and Technology, 2010)
In this present paper Antibacterial activity of Salacia oblonga Wall plant was evaluated with some pathogenic bacteria like (Staphylococcus epidermidis, Enterococcus faecalis, Bacillus subtilis, Escherichia coli, Salmonella typhi, Klebsiella pneumonia, Enterobacter cloacae, Pseudomonas aeruginosa). Salacia oblonga plant extract was prepared by using ethylacetate solvent by comparing with the Amikacin (Antibiotic). Eight bacterial species were tested for the antibacterial study. Out of eight, three are Gram positive (Staphylococcus epidermidis, Enterococcus faecalis, Bacillus subtilis) and remaining five are Gram negative (Escherichia coli, Salmonella typhi, Klebsiella pneumonia, Enterobacter cloacae, Pseudomonas aeruginosa).Â The root extract of Salacia oblonga showed the highest zone of inhibition against Bacillus subtilis than aerial part.